Motivation as predictor toward students' mastery learning in physical education and sport engagement / Nabilah Abu Safian - Abu Safian, Nabilah (Faculty of Education, 2014)
The purpose of this study was to investigate the level of student in three area namely are motivation in Physical Education, mastery learning and sport engagement also to determine whether motivation can be predictor to students’ mastery learning in Physical Education and sport engagement. Sixty respondents in range of 15 years old to 7 years old were conveniently chosen to participate in this study. The respondents are students from Sekolah Menengah Kebangsaan Seksyan 24 (1) Shah Alam. Set of questionnaires consist of 47 items were distributed and have been analyzed using the IBM Statical Package for Social Science (SPSS) Statistics v. 20.Descriptive analysis has been used to find the level of student motivation, their mastery in learning Physical Education and sport engagement. Simple linear regressions otherwise used to predict the relationship between two variables namely are learning domains and sport engagement. Overall of the findings, shows that there have significant differences between motivation (Predictor) and both independent variables namely students’ mastery learning in Physical Education and sport engagement. Researchers also presented a number of recommendations to attract students in Physical Education classes and get engage in sports.